PENGARUH KONSENTRASI DAN BAGIAN TEPUNG BATANG, DAUN DAN BUNGA KECOMBRANG (Nicolaia spesiosa Horan) TERHADAP JUMLAH MIKROBA CUKO PEMPEK SELAMA PENYIMPANAN - Andriansyah, Riki; Muchsiri, Mukhtarudin; Alhanannasir, Alhanannasir (Universitas Muhammadiyah Palembang, 2017)
The aims of research to determined the total microbial of cuko pempek by preservatives such as flour stems, leaves and flowers kecombrang and to determine the organoleptic properties of the color, flavor and aroma cuko pempek before and after 12 days of storage. This research has been conducted in labaratorium Faculty of Agriculture, University of Muhammadiyah Palembang and the laboratory of Research and Industry Standards Palembang in July until August 2016. This study uses a randomized block design (RAK) arranged as factorial with the addition of flour treatment factor stems, leaves and flowers kecombrang on making cuko pempek which consists of three groups and consists of nine treatment factors were repeated three times. The parameters were observed in the study include chemical analysis (pH), microbiological (TPC and Gram Strain) and organoleptic (color, taste and aroma) cuko pempek based preference level using hedonic scale. Concentration flour stems, leaves and flowers kecombrang very significant effect on the number of microbes and organoleptic cuko pempek after storage. Treatment K3C3 (flour interest kecombrang 3%) had the lowest total microbes after 12 days of storage with the value of the average 1,10x 10Â² sel/g. best value preference level of the color, flavor and aroma cuko pempek after 12 days of storage are in treatment K3C3 (flour flower kecombrang 3%) with the average value color 3,55, flavor 4,00 dan aroma 3,75.